Cardiovascular autonomic testing performed with a new integrated instrumental approach is useful in differentiating MSA-P from PD at an early stage. Issue 5 (May 2015) - Baschieri, Francesca; Calandra-Buonaura, Giovanna; Doria, Andrea; Mastrolilli, Francesca; Palareti, Aldopaolo; Barletta, Giorgio; Solieri, Laura; Guaraldi, Pietro; Martinelli, Paolo; Cortelli, Pietro
Abstract Objective To evaluate whether a battery of cardiovascular autonomic tests (Ewing's battery, EB) performed with a new integrated instrumental approach is useful in differentiating multiple system atrophy with predominant parkinsonism (MSA-P) from Parkinson's disease (PD) at an early stage. Methods We retrospectively analyzed EB tests of all the patients (n = 99) with a parkinsonian syndrome referred to our clinic who performed EB during the first diagnostic workup and were subsequently evaluated at least once a year until a final diagnosis of MSA-P (n = 34) or PD (n = 65). Thirty-eight controls matched for age and sex were included. EB consisted of head-up tilt test (HUTT), Valsalva manoeuvre (VM), deep breathing, and sustained handgrip whose correct execution and results were checked and obtained automatically. Results were compared between groups. Discriminant analysis was performed to identify MSA-P or PD patients. Results Orthostatic hypotension was found in 22 MSA-P and 3 PD patients. Cardiovascular reflexes indices were significantly more affected in MSA-P compared to PD and controls. EB presented a 91% sensitivity and 94% specificity in the differentiation of MSA-P and PD. HUTT + VM presented a 91% sensitivity and 92% specificity. Conclusions Our results suggest that EB or HUTT + VM performed with an integrated instrumental approach and analyzed with the discriminant procedure may distinguish MSA-P from PD at an early stage and might improve the accuracy of current diagnostic criteria. However, a validation in separate samples and prospective studies is needed.